2018
DOI: 10.1177/1359105318800788
|View full text |Cite
|
Sign up to set email alerts
|

Using Rasch analysis to investigate the validity of the Everyday Discrimination Scale in a national sample

Abstract: The Everyday Discrimination Scale (EDS) is a widely used measure of discrimination. Rasch analysis was used to examine the psychometric properties of the EDS based on a national sample ( N = 2666). Items largely fit the Rasch model and yielded excellent separation and item reliability. However, severe floor effects were observed. Implications are discussed for use of the scale in populations that experience low levels of discrimination. An ordinal-to-interval conversion table for the EDS is also provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
(45 reference statements)
1
8
0
Order By: Relevance
“…However, we believe that the benefits of our study outweigh the statistical deficiencies. In sum, giving previous studies showed ethnic/racial differences in RED measures (Berenbon, 2020;Lewis et al, 2012;Stucky et al, 2011), researchers should be cautious making racial/ ethnic group comparisons. Last, although our study adds a large and diverse group of adolescents to a literature that has focused on adults, age and our location in a large urban area may limit the generalizability of our results.…”
Section: Implications and Conclusionmentioning
confidence: 94%
See 2 more Smart Citations
“…However, we believe that the benefits of our study outweigh the statistical deficiencies. In sum, giving previous studies showed ethnic/racial differences in RED measures (Berenbon, 2020;Lewis et al, 2012;Stucky et al, 2011), researchers should be cautious making racial/ ethnic group comparisons. Last, although our study adds a large and diverse group of adolescents to a literature that has focused on adults, age and our location in a large urban area may limit the generalizability of our results.…”
Section: Implications and Conclusionmentioning
confidence: 94%
“…The following section reviews studies that have applied IRT methods to the EDS (Berenbon, 2020; Lewis et al, 2012; Stucky et al, 2011), and discusses how the current study contributes to this body of work. It is worth mentioning that the studies reviewed here examine the EDS at the person level, with a particular focus on measurement invariance across certain groups (e.g., gender and race).…”
Section: Measuring Racial/ethnic Discriminationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these measurements were validated for some populations, but not all different populations. For instance, Gonzales et al (2016) found that the EDS was valid among American Indians and Alaska Natives while Berenbon (2018) found that the EDS might not work for someone who does not experience less discrimination. To understand the experience of discrimination and microaggression among different groups of individuals, including Asians, future research should pay special attention to developing validated scales tailored to specific populations.…”
Section: Discussionmentioning
confidence: 99%
“…The last item assesses participants' perception regarding the main reason for PED, listing age, ancestry or national origin, education or income level, gender, height, physical appearance, race, religion, sexual orientation, and weight. The EDS has been found to have appropriate validity using a Rasch analysis in a national sample (Berenbon, 2020) and high internal consistency in college student samples ( α = 0.91; Hatzenbuehler et al, 2011). Internal consistency reliability for our sample is presented in Table 1.…”
Section: Methodsmentioning
confidence: 99%